2009
DOI: 10.1080/08830180903093788
|View full text |Cite
|
Sign up to set email alerts
|

Can Proliferation Signal Inhibitor-Induced Tregs Really Reflect Transplantation Tolerance in Clinical Solid Organ Transplantation?

Abstract: Exploring new immunosuppressive strategies inducing donor-specific hyporesponsiveness is a great challenge in transplantation. For this purpose, monitoring the alloimmune response is a critical step to carrying out protolerogenic immunosuppressive protocols. Regulatory T cells (Tregs), known as controlling various immune responses, were found to play an important part in allograft transplant tolerance. It is said that Rapamycin (RAPA), one of the proliferation signal inhibitors (PSIs), could achieve true toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It has been reported that in vivo rapamycin administration contributed to selective activation and expansion of CD4 + CD25 + Foxp3 + Treg, not only in peripheral blood, but also, in secondary lymphoid organs and grafts, both of which merit graft survival. 15,[25][26] Therefore, it is reasonable to deduce that the increased numbers of CD4 + CD25 + Foxp3 + Treg found in draining lymph nodes and corneal grafts play a pivotal role in inhibiting graft rejection after allogenic keratoplasty. Moreover, previous research has observed that the number of Tregs increased shortly after rapamycin therapy was stopped, and then decreased gradually.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in vivo rapamycin administration contributed to selective activation and expansion of CD4 + CD25 + Foxp3 + Treg, not only in peripheral blood, but also, in secondary lymphoid organs and grafts, both of which merit graft survival. 15,[25][26] Therefore, it is reasonable to deduce that the increased numbers of CD4 + CD25 + Foxp3 + Treg found in draining lymph nodes and corneal grafts play a pivotal role in inhibiting graft rejection after allogenic keratoplasty. Moreover, previous research has observed that the number of Tregs increased shortly after rapamycin therapy was stopped, and then decreased gradually.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of Tm cells to immune suppression might be inherent in their nature, as they are highly proliferative, with minimum requirements for antigen stimulation and co‐stimulatory activation . In addition, they are generally resistant to apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…In inbred rodent models, long‐term graft tolerance can be induced by various approaches including immunosuppressive drug treatment, preestablishment of mixed chimerism by bone marrow transplantation, T cell depletion, T cell signal blockade and induction of regulatory T cell (Tregs) . Notably, the manipulation of Tregs has been extensively shown as promising .…”
Section: Introductionmentioning
confidence: 99%